PENGEMBANGAN METODE LOOP-MEDIATED ISOTHERMAL AMPLIFICATION OF DNA DAN APLIKASINYA UNTUK DETEKSI KOI HERPES VIRUS PADA BEBERAPA JENIS IKAN - Murwantoko Murwantoko; Triyanto Triyanto; Dimas A. Pamungkas (Universitas Gadjah Mada, 2010)
The purposes of this experiment were to establish loop-mediated isothermal ampliﬁcation of DNA ( LAMP) method and its application to observe the presence and duration of koi herpes virus ( KHV) in freshwater ﬁshes after infection. The infection was carried out using 4-6 cm length of java barb (Barbodes gonionotus), grass carp (Ctenoparingodon idella), gold ﬁsh (komet) (Carassius auratus), tambaqui (Colossoma macropomum) and koi (Cyprinus carpio koi) ﬁshes. Fishes were infected intraperitoneally with KHV inoculums and 2 ﬁshes were sampled everyday. DNA was extracted from gill and used for diagnosis with LAMP assays. The result of this experiment showed LAMP assay can be established and gave 100 times more sensitive than conventional PCR assay. Koi was conﬁrmed as a host of KHV. Java barb, tambaqui, gold ﬁsh and grass carp can serve as vector for KHV and the presence of KHV was detected in java barb and tambaqui for 4 days, goldﬁsh and grass carp for 5 days after infection.